Penerapan Penyusunan Laporan Keuangan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada Usaha Ayam Bakar Pulo - wulan sari, nidia; indonesia, indonesia (LPPM UNU CIREBON, 2025)
This study aim to apply financial statement preparation in accordance with the Financial Accounting Standars For Micro, Small, and Medium Entities (SAK EMKM) at Usaha Ayam Bakar Pulo. Usaha Ayam Bakar Pulo has not yet implemented standard financial recording and reporting, so its financial statements do not reflect the actual condition of the business. The research method used is a descriptive qualitative method with a case study approach. Data was obtained through observation, interviews, and documentation at the Pulo Grilled Chicken Business. The results of the study indicate that the application of SAK EMKM can assist the business in preparing financial position statements, income statements, and notes to the financial statements in a simple yet standard-compliant manner. In the financial position report, the assets owned by the Pulo Grilled Chiken Business amount to Rp. 54.476.000,-, which is equal to the total liabilities and equity of Rp. 54.476.000,-. In the income statement, the net profit earned during March 2025 wa Rp. 51.976.000. This also enhances the business owner’s understanding of the importance of financial statements in decision-making and increases the likelihood of accessing financing.